2010
DOI: 10.1002/cae.20485
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on factors influencing the effectiveness of algorithm visualization

Abstract: ABSTRACT:The determination of the factors influencing the effectiveness of algorithm visualization poses an interesting research question. In this paper, we present the results of a longitude empirical study regarding this question. The study was based on an evaluation of the Visual LinProg educational tool inside classrooms. Visual LinProg is a web-based educational tool, which solves linear programming problems using animation and visualization techniques. Visual LinProg was developed to be used in linear pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Reference [22] itemized AV principles according to Visual LinProg (AV web-based educational tool) (see Figure 2.5), they are:…”
Section: The Data Structure Learning (Dsl)mentioning
confidence: 99%
“…Reference [22] itemized AV principles according to Visual LinProg (AV web-based educational tool) (see Figure 2.5), they are:…”
Section: The Data Structure Learning (Dsl)mentioning
confidence: 99%
“…There are many case studies and applications in the literature regarding the use of computer‐based educational tools indicating optimistic and positive results . Among these, Deliktas presented a novel teaching and learning methodology enhanced with computer technology and indicated the importance of visual components in education with several very interesting examples.…”
Section: Introductionmentioning
confidence: 99%
“…webNetPro could be viewed as a powerful supplement to traditional instruction techniques and be used without significant difficulties in distance education. Lazaridis et al discussed some new results on the factors influencing the effectiveness of Algorithm Visualization (AV) applications and the factors influencing the understanding of the revised simplex algorithm. It was found that the most important factors influencing the understanding of the proposed algorithm by the students was the use of animated pseudo‐code steps and of textual observation aids during the solution process of a problem in Visual LinProg.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic meta-study of 24 experimental studies can be found in [4]. Results of empirical study aimed at the determination of factors influencing the effectiveness of algorithm visualization are published in [5]. Another example is the study with the objective to determine learning advantage of the interactive prediction facility provided by the courseware containing algorithm animations and data structure visualizations [6].…”
mentioning
confidence: 99%
“…Modern approaches to software visualization were brought in the 1980's by the introduction of system BALSA (Brown & Sedgewick, Brown University, USA) [12]. Some of contemporary solutions include systems like TRAKLA2 3 , ANIMAL 4 [13], JAWAA 5 or Algorithms In Action 6 . Concise overview of development in the area of software visualization we provided in [14], so it is not our intention to analyse this topic within the paper.…”
mentioning
confidence: 99%